THE ROLE OF HABITATIVE ACTIVITIES ON THE DEVELOPMENT OF THE MORAL CHARACTER OF TPQ DARUSSALAM STUDENTS IN KARANGGONDANG VILLAGE, WONOSOBO - Wissda Azzahro Chairunisa; Ahmad Zuhdi; Muhammad Saefullah (Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2026)
This study focuses on the role of habituation activities in the moral development of students at the Darussalam Islamic Boarding School (TPQ) in Karanggondang Village, Wonosobo. A descriptive qualitative method was employed. Data were collected through interviews, observations, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. This study found that routine and ongoing habituation activities can shape positive student behavior. These activities include habituation in greeting, praying, reading the Quran, and instilling discipline, responsibility, and good manners. Students' moral development was observed gradually, marked by increased discipline, politeness, and awareness in worship and social interactions. The success of habituation activities was supported by the roles of teachers, parents, and the community. Obstacles encountered included a lack of consistency among some students and limited support at home. Therefore, habituation activities play a crucial role in students' moral development and require collaboration between institutions, families, and the community